CRF1 Receptor Signaling via the ERK1/2-MAP and Akt Kinase Cascades: Roles of Src, EGF Receptor, and PI3-Kinase Mechanisms - Parra-Mercado, G. Karina; Fuentes-Gonzalez, Alma M.; Hernandez-Aranda, Judith; Diaz-Coranguez, Monica; Dautzenberg, Frank M.; Catt, Kevin J.; Hauger, Richard L.; Olivares-Reyes, J. Alberto (Frontiers in Endocrinology, 2019)
In the present study, we determined the cellular regulators of ERK1/2 and Akt signaling pathways in response to human CRF1 receptor (CRF1R) activation in transfected COS-7 cells. We found that Pertussis Toxin (PTX) treatment or sequestering Gβγ reduced CRF1R-mediated activation of ERK1/2, suggesting the involvement of a Gi-linked cascade. Neither Gs/PKA nor Gq/PKC were associated with ERK1/2 activation. Besides, CRF induced EGF receptor (EGFR) phosphorylation at Tyr1068, and selective inhibition of EGFR kinase activity by AG1478 strongly inhibited the CRF1R-mediated phosphorylation of ERK1/2, indicating the participation of EGFR transactivation. Furthermore, CRF-induced ERK1/2 phosphorylation was not altered by pretreatment with batimastat, GM6001, or an HB-EGF antibody indicating that metalloproteinase processing of HB-EGF ligands is not required for the CRF-mediated EGFR transactivation. We also observed that CRF induced Src and PYK2 phosphorylation in a Gβγ-dependent manner. Additionally, using the specific Src kinase inhibitor PP2 and the dominant-negative-SrcYF-KM, it was revealed that CRF-stimulated ERK1/2 phosphorylation depends on Src activation. PP2 also blocked the effect of CRF on Src and EGFR (Tyr845) phosphorylation, further demonstrating the centrality of Src. We identified the formation of a protein complex consisting of CRF1R, Src, and EGFR facilitates EGFR transactivation and CRF1R-mediated signaling. CRF stimulated Akt phosphorylation, which was dependent on Gi/βγ subunits, and Src activation, however, was only slightly dependent on EGFR transactivation. Moreover, PI3K inhibitors were able to inhibit not only the CRF-induced phosphorylation of Akt, as expected, but also ERK1/2 activation by CRF suggesting a PI3K dependency in the CRF1R ERK signaling. Finally, CRF-stimulated ERK1/2 activation was similar in the wild-type CRF1R and the phosphorylation-deficient CRF1R-Δ386 mutant, which has impaired agonist-dependent β-arrestin-2 recruitment; however, this situation may have resulted from the low β-arrestin expression in the COS-7 cells. When β-arrestin-2 was overexpressed in COS-7 cells, CRF-stimulated ERK1/2 phosphorylation was markedly upregulated. These findings indicate that on the base of a constitutive CRF1R/EGFR interaction, the Gi/βγ subunits upstream activation of Src, PYK2, PI3K, and transactivation of the EGFR are required for CRF1R signaling via the ERK1/2-MAP kinase pathway. In contrast, Akt activation via CRF1R is mediated by the Src/PI3K pathway with little contribution of EGFR transactivation.